Preserving Malay architectural heritage through virtual reconstruction - Ibrahim N.; Azmi K.A. (2023)
Preserving architectural heritage is a challenging and costly task. Digital preservation helps to both reduce costs and make it portable. This paper describes our experience in producing a 3D model of Rumah Tok Su; which is a traditional Malay house, situated in Kedah, Malaysia. The aim of this project is to capture the essence of architectural heritage via still images that are rendered to highlight its beauty and significance. 2013 IEEE.